Pengaruh Penggunaan Abu Cangkang Lokan, Serbuk Bata Merah dan Aditif Anti Pengelupasan pada AC-BC - Samsul Bahri (UNIVERSITAS LAMPUNG, 2016)
This study aims to find a right formula of asphalt concrete binder course (AC-BC) hotmix by adding the ash of lokan’s shell (ACL), red brick powder (SBM) and anti stripping agent. Chemical analysis for ACL and SBM used SEM-EDX analysis. Hotmix sample testing used Marshall method. The results showed that the ACL contains 34,77% carbon and 65,23% calcium oxide. SBM was containing 34,09% alumina, 42,55% silica dioxide, 0,73% potassium oxide, 1,98% titanium (IV) oxide and 20,65% ferrous oxide. The addition of filler ACL SBM 50% + 50% from 10% cement filler; the ingredient of anti stripping agent wetfix was 0,3% optimum asphalt content (OAC), increasing the value of stability and flow mix AC-BC amounted to 51,5% and 41,5%. Anova test results showed that the value of F for stability is of 9,21, the value of F for flow amounted to 19,19. Ftable at 99% confidence level refers to the value of 7,82. This proves that the addition of ash shell seashell, red brick powder and additive anti sloughing have significant effect on the stability and flow value mix AC-BC. Durability and flexibility of road construction types AC-BC for the better.